2010
DOI: 10.1016/j.spl.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

A note on bootstrap approximations for the empirical copula process

Abstract: It is well known that the empirical copula process converges weakly to a centered Gaussian field. Because the covariance structure of the limiting process depends on the partial derivatives of the unknown copula several bootstrap approximations for the empirical copula process have been proposed in the literature. We present a brief review of these procedures.Because some of these procedures also require the estimation of the derivatives of the unknown copula we propose an alternative approach which circumvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 14 publications
6
55
0
Order By: Relevance
“…, ξ n,n satisfies assumptions (M1), (M2) and (M3). From a practical perspective, for the function ϕ, we considered the Bartlett and Parzen kernels κ B and κ P , as well as κ U,6 and κ U, 8 , where κ U,p is the density function of the sum of p independent uniforms centered at 0, normalized so that it equals 1 at 0, and rescaled to have support (−1, 1). The functions κ U,6 and κ U,8 are represented in Figure 1.…”
Section: The Covariance Matrix Approachmentioning
confidence: 99%
“…, ξ n,n satisfies assumptions (M1), (M2) and (M3). From a practical perspective, for the function ϕ, we considered the Bartlett and Parzen kernels κ B and κ P , as well as κ U,6 and κ U, 8 , where κ U,p is the density function of the sum of p independent uniforms centered at 0, normalized so that it equals 1 at 0, and rescaled to have support (−1, 1). The functions κ U,6 and κ U,8 are represented in Figure 1.…”
Section: The Covariance Matrix Approachmentioning
confidence: 99%
“…Theorem 1.12.4 in Van der Vaart and Wellner (1996). The process B C can be approximated by multiplier bootstrap methods, see Bücher (2011);Bücher and Dette (2010); Rémillard and Scaillet (2009);Segers (2011). More precisely, let ξ 1 , .…”
Section: A Multiplier Bootstrap Approximationmentioning
confidence: 99%
“…Some precedent studies have used the bootstrap method to approximate the limiting distribution. Bücher and Dette [25] compared the finite sample properties of the various bootstrap methods proposed in the literature and concluded that the procedure proposed by Rémillard and Scaillet [24] yields the best results in most cases. In this study, we consider the multiplier bootstrap approach proposed by Rémillard and Scaillet [24].…”
Section: Lemmamentioning
confidence: 99%
“…To overcome this problem, several authors have suggested bootstrap methods for approximating the Kiefer process. We refer to Fermanian et al [23], Rémillard and Scaillet [24], Bücher and Dette [25], Bouzebda [26] and the references therein for more details. In this study, we also utilize the bootstrap method to deal with this difficulty.…”
Section: Introductionmentioning
confidence: 99%